Sugar Transporter ZjSWEET2.2 Mediates Sugar Loading in Leaves of Ziziphus jujuba Mill - Geng, Yanqiu; Wu, Mengjia; Zhang, Chunmei (Frontiers in Plant Science, 2020)
In plants, sugar transporters play an important role in the allocation of sugars from cells in source organs to cells in sink organs. Hence, an understanding of the molecular basis and regulation of assimilate partitioning by sugar transporters is essential. Leaves are the main source of photosynthetic products. In jujube (Ziziphus jujuba Mill.), the mechanisms regulating initial sugar unloading in leaves are still unclear. In this study, an expression profiling analysis showed that ZjSWEET2.2, encoding a sugar transporter in the SWEET family, is highly expressed in leaves. Over-expression of ZjSWEET2.2 increased carbon fixation in photosynthetic organs. Our analyses showed that ZjSWEET2.2 encodes a plasma membrane-localized sugar transporter protein. Its expression levels were found to be suppressed under drought stress and by high concentrations of exogenous sugars, but increased by low concentrations of exogenous sugars. Finally, DNA sequence analyses revealed several cis-elements related to sugar signaling in the promoter of ZjSWEET2.2. Together, these results suggest that ZjSWEET2.2 functions to mediate photosynthesis by exporting sugars from photosynthetic cells in the leaves, and its gene expression is regulated by sugar signals.